Narrar em nosso tempo : experiência e saúde no trabalho em educação - Chambela, Suzana Maria Gotardo (2018)
This work is dedicated to the issue of narratives, in accordance with the thinking of Walter Benjamin, presenting it in its dimension of collective production linked to a living experience woven in community. It is an effort to make explicit its health effects in the scope of work in education, considering a wide range of productions that relate it to illness processes, which must be analyzed in close connection with the capitalistic mode of production and the divisions through which it operates. The argumentation of this thesis is built from the insertion in research-intervention practices undertaken by the Training and Research Program in Health and Work (Pfist), in its crossings with the Forum of Health Committees of the Education Worker (Forum Cosate) - which constitutes a strategy for the creation of such commissions in the municipality of Serra, Espirito Santo State (ES). These are aimed at fostering collective coping strategies at organizational modes that produce suffering, shifting it from an individualized relationship and producing shared referrals that increase the capacity for creation and the power to act at work. "Narrating in our times" expresses the bet in a movement to produce fractures in hegemonic ways of living the work, through an investment of attention in the dimension of communicability triggered by a time of now (Jetztzeit), the time of our action in this world, that makes, in a jump, to find past and present as a possibility of operating displacements in the conformations of the real. It also expresses the investment in the transmissibility of the experience constituted in care production exercises with the practices within the framework of Pfist, the Forum Cosate and the experiments with these commissions in Serra.